2021
DOI: 10.1371/journal.pgph.0000008
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the mortality burden of large scale mining projects—Evidence from a prospective mortality surveillance study in Tanzania

Abstract: We set up a mortality surveillance system around two of the largest gold mines in Tanzania between February 2019 and February 2020 to estimate the mortality impact of gold mines. Death circumstances were collected using a standardized verbal autopsy tool, and causes of death were assigned using the InSilicoVA algorithm. We compared cause-specific mortality fractions in mining communities with other subnational data as well as national estimates. Within mining communities, we estimated mortality risks of mining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, capturing wider social conditions of death (e.g. occupational and environmental) and how these interact with circumstances and events at and around time of death is a priority [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, capturing wider social conditions of death (e.g. occupational and environmental) and how these interact with circumstances and events at and around time of death is a priority [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through their work, ASMs are exposed to numerous toxic substances including silica dust, which can cause silicosis, a risk factor for developing TB [ 11 ]. A recent study showed that non-HIV infectious diseases (respiratory infections including tuberculosis ) were the leading cause of mortality in two mines in Geita and Shinyanga provinces [ 12 ]. Many female sex workers (FSWs) also live in and around the same informal settlements.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies found that miners have higher HIV prevalence in Lesotho and Eswatini, lower in Tanzania, whereas in Zambia and Zimbabwe, only minor differences were found [ 6 , 11 , 15 ]. Contrarily, higher mortality rates of HIV were found among male miners in Tanzania compared with other community members [ 16 ]. Conversely, sexually transmitted diseases, including HIV/AIDS, were less frequently reported in metal extraction areas [ 17 ].…”
Section: Introductionmentioning
confidence: 99%